2018
DOI: 10.21836/pem20180103
|View full text |Cite
|
Sign up to set email alerts
|

Non-antibiotic treatment of equine endometritis

Abstract: Equine endometritis is an important cause of infertility, associated with major economic losses to the horse industry worldwide. An evolving understanding of the complexity of the disease has resulted in new treatment approaches to combat the effect on fertility through alternative non-antibiotic therapies. The objective of this article is to review some of the commonly used non-antibiotic treatment options for equine endometritis. The most recent literature on treatment options with non-antibiotic antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Ecbolic drugs such as OT and PG can stimulate uterine contractions and help in the excretion of any debris or accumulations from the uterus, which promotes uterine clearance [ 17 ]. In comparisons of PG and OT, the effect of PG on myometrial activity has been determined to be longer than that of OT [ 29 , 30 ]. OT induces high-amplitude uterine contractions for approximately 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Ecbolic drugs such as OT and PG can stimulate uterine contractions and help in the excretion of any debris or accumulations from the uterus, which promotes uterine clearance [ 17 ]. In comparisons of PG and OT, the effect of PG on myometrial activity has been determined to be longer than that of OT [ 29 , 30 ]. OT induces high-amplitude uterine contractions for approximately 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response of the endometrium of mares has been extensively investigated [ 176 , 177 ]. A positive effect of corticosteroid administration on the uterine immune response has been reported in several studies [ 176 , 177 , 178 , 179 ], which may ultimately improve fertility of animals.…”
Section: Approaches To Circumvent Antibiotic Resistancementioning
confidence: 99%
“…The immune response of the endometrium of mares has been extensively investigated [ 176 , 177 ]. A positive effect of corticosteroid administration on the uterine immune response has been reported in several studies [ 176 , 177 , 178 , 179 ], which may ultimately improve fertility of animals. For example, administration of dexamethasone at breeding was found to improve pregnancy rates in mares with a history of post-mating endometritis [ 180 ].…”
Section: Approaches To Circumvent Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of a variety of treatment options ( Table 1 ), evidence-based reports on their effectiveness are lacking ( 66 ). A recent survey of equine practitioners in Germany concluded that most still mainly use systemic antibiotic therapy for equine endometritis ( 67 ).…”
Section: Treatment Optionsmentioning
confidence: 99%